LANGUAGE STYLE IN TV INTERVIEW: IMPLICATION FOR TEACHING SOCIOLINGUISTIC COMPETENCE - Afriza, Irkhas Ziana Rizqi; Martina, Martina (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
This article is intended to clearly describe the implications of teaching sociolinguistic competence from studying language style in TV interviews and obtaining data from research problems. The style of language owned by a person is part of diction that is closely related to individual or characteristic expressions or has high artistic value. Therefore, language style becomes a way of expressing one's thoughts through language specifically that can show the soul and personality of language users. In this study, several language styles were detected in TV interviews: casual, intimate, formal, and consultative. The frozen style was not found. The finding implies the teaching of Sociolinguistic competence as language learners can understand the way language style blends in language situations, reflecting the status of the relationship between the sender and the recipient of the message. In addition, language learners can acquire the language style in the social context taking place in the TV interview.